Burns: modified metabolism and the nuances of nutrition therapy. (2nd March 2020) - Houschyar, Madeline; Borrelli, Mimi R; Tapking, Christian; Maan, Zeshaan N; Rein, Susanne; Chelliah, Malcolm P; Sheckter, Clifford C; Duscher, Dominik; Branski, Ludwik K; Wallner, Christoph; Behr, Bjö; Lehnhardt, Marcus; et al.
Abstract : Objective: To review the effects of burn injury on nutritional requirements and how this can best be supported in a healthcare setting. Method: A literature search for articles discussing nutrition and/or metabolism following burn injury was carried out. PubMed, Embase and Web of Science databases were searched using the key search terms 'nutrition' OR 'metabolism' AND 'burn injury' OR 'burns'. There was no limitation on the year of publication. Results: A total of nine articles met the inclusion criteria, the contents of which are discussed in this manuscript. Conclusion: Thermal injury elicits the greatest metabolic response, among all traumatic events, in critically ill patients. In order to ensure burn patients can meet the demands of their increased metabolic rate and energy expenditure, adequate nutritional support is essential. Burn injury results in a unique pathophysiology, involving alterations in endocrine, inflammatory, metabolic and immune pathways and nutritional support needed during the inpatient stay varies depending on burn severity and idiosyncratic patient physiologic parameters.